Implementasi Pendidikan Karakter Peduli Sosial melalui Program Koin infaq di MTs Hasan Kafrawi Mayong Jepara - Jamal Lutfi; Taufiqurrahman Taufiqurrahman (Universitas Muhammadiyah Mataram, 2026)
Abstract: Character education has become an important focus in strengthening educational quality as it emphasizes not only academic achievement but also students’ social development. One emerging approach is school-based philanthropy programs that provide students with direct social experiences. This study aims to analyze the implementation of the Koin Infaq Program as a medium for developing students’ social care character in an Islamic junior secondary school. The study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the Koin Infaq Program functions not merely as a school philanthropy activity but also as a mechanism for internalizing social care values through habituation, active student participation, school collaboration, and teacher role modeling. The program contributed to the development of empathy, social responsibility, and sharing behavior among students. Although challenges remain in maintaining participation consistency and deepening value internalization, reflective and participatory strategies strengthened the effectiveness of character education.Abstrak: Pendidikan karakter menjadi salah satu fokus penting dalam penguatan kualitas pendidikan karena tidak hanya menekankan pencapaian akademik, tetapi juga pembentukan sikap sosial peserta didik. Salah satu pendekatan yang berkembang adalah melalui program filantropi berbasis sekolah yang memberikan pengalaman sosial secara langsung kepada siswa. Penelitian ini bertujuan menganalisis implementasi Program Koin Infaq sebagai media pembentukan karakter peduli sosial siswa di sebuah madrasah. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa Program Koin Infaq berfungsi tidak hanya sebagai kegiatan filantropi sekolah, tetapi juga sebagai sarana internalisasi nilai kepedulian sosial melalui pembiasaan, keterlibatan aktif siswa, kolaborasi sekolah, dan keteladanan guru. Program ini berkontribusi terhadap peningkatan empati, tanggung jawab sosial, serta kebiasaan berbagi pada peserta didik. Meskipun menghadapi tantangan dalam menjaga konsistensi partisipasi dan pendalaman makna kegiatan, sekolah mampu mengembangkan strategi reflektif dan partisipatif untuk memperkuat efektivitas pendidikan karakter.